Local transport kinetics of glucose during acute and chronic nicotine infusion in rat brains - Duelli, Roman; Staudt, Richard Erhard; Maurer, Martin H.; Kuschinsky, Wolfgang (Journal of neural transmission, 1998)
Acute and chronic infusion of nicotine is known to result in a distinct increase in local cerebral glucose utilization (LCGU) in several brain structures. The present study addresses the question whether this increase in LCGU is paralleled by a local change in glucose transport in rat brain. Nicotine was infused either acutely for 3 hours or chronically by osmotic minipumps for one week. Local rate constants for glucose transport were measured in brain cryosections using the 3-O-[14C]methylglucose method. Local rate constants K1 and k2 were lower in part of the brain structures during acute (−10% to −20%) and in nearly all structures during chronic (−39% to −41%) nicotine. The finding of a decreased glucose transport during chronic nicotine was confirmed by additional experiments of 3-O-[14C]methylglucose transfer in an epithelial cell culture. It is concluded that acute and chronic nicotine infusion results in decreased glucose transport although LCGU is either unchanged or increased.